Security in computing - Pfleeger, Charles P., 1948-; Pfleeger, Shari Lawrence (Pearson, 2002)
The classic guide to information security-fully updated for the latest attacks and countermeasures Security in Computing, Third Edition systematically demonstrates how to control failures of confidentiality, integrity, and availability in applications, databases, operating systems, and networks alike. This sweeping revision of the field's classic guide to computer security reflects today's entirely new generation of network- and Internet-based threats and vulnerabilities, and offers practical guidance for responding to them. Updated to cover wireless security, intrusion detection, AES, DRM, biometrics, honeypots, online privacy, and more Security in Internet-based, distributed, desktop and traditional centralized applications New attacks, including scripted vulnerability probing, denial of service, and buffer overflows-with symptoms and cures Clear, accessible introduction to cryptography-without sophisticated math Up-to-the-minute explanations of digital signatures, certificates, and leading-edge quantum cryptography Thoroughly revamped coverage of software engineering practices designed to enhance program security Expanded coverage of risk management, contingency planning, and security policies Detailed presentation of protection in general-purpose and trusted operating systems Extensive pedagogical resources: end-of-chapter reviews and exercises, lists of key terms, and authoritative references Exceptionally clear and easy to understand, the book covers not only technical issues, but also law, privacy, ethics, and the physical and administrative aspects of security. The companion website (http://www.phptr.com/pfleeger/) contains additional information, book updates, and instructor's resources.